Measuring the Impact of Brand Equity on Company Performance: A Study on the Mobile Phone Brands in The Klang Valley, Malaysia - Hong, Amelia Woon Ai (2007)
Building and managing brand equity is emphasised in many consumer goods industry to ensure their success. The key to this success is understanding brand equity and managing it to achieve good financial results. Among the many methods of examining brand equity, this study chose the customer-based brand equity method conceptualised by Aaker (1991) and tested by Yoo and Donthu (2001). The aim of this study is to examine the dimensions of brand equity which are brand awareness, brand loyalty, perceived quality and brand image and how these dimensions affect the performance of the mobile phone companies in Malaysia – in particular the four big mobile phone brands - Nokia, Samsung, Sony Ericsson and Motorola. A questionnaire was developed to which a total of 308 respondents from the Klang Valley participated. The data collected from the survey were analysed using a statistical software application called SPSS. SPSS was used to measure the reliability, factor analysis and regression analysis. An interview was also conducted with a key personnel from the mobile phone industry in Malaysia. The results of the empirical study showed that brand equity has a positive effect on company performance. Brand awareness, brand loyalty and brand image are found to have an impact on company performance. Perceived quality however, does not impact company performance. Other than brand equity, product design and product features are important drivers of company performance as discovered during the interview conducted. In conclusion, the results of this study imply that strong brand equity is important so that the brand comes into the evoked set of choice of the customers. When the brand is strong enough to be included into the set of choices of the customer, then what moves the customers to purchase the brand is largely dependent on product design and product features. A discussion on the implications was put forth and recommendations were given in this study.